Association of TGF-Β1 Gene Polymorphism with Oral Submucous Fibrosis - Muhammad Akram, Sadiq Ali, Muhammad Nauman, Ali Abu Bakar, Abbas Raza Shah, Urooj Kirmani, Navaira Tariq, (Pakistan Journal of Medical & Health Sciences, 2025)
Objective: To evaluate the association of TGF-β1 gene polymorphism with oral submucous fibrosis. Study design: Case-control study Place and duration of study: Department of Human Genetics and Molecular Biology, The University of Health Sciences Lahore and Department of Oral & Maxillofacial Surgery, Medical University of Montmorency, Lahore. Methodology: Two hundred participants were divided into two groups of 100 participants, those with normal mucous membranes and those with clinically confirmed oral sub-mucosal fibrosis (OSF). Total genomic DNA was isolated by drawing blood samples. Results: There was a significant difference in the genotypic frequency distributions of TGF-β1 gene polymorphisms between OSF patients and controls. Oral sub-mucosal fibrosis patients had a higher percentage of the CC genotype (P=0.040) compared to controls. In OSF cases, the proportion of TT, CT, and CC for the TGF-β1 gene was 10.0%, 34%, and 56%, respectively, compared to normal controls which had 16%, 49%, and 35% (P=<0.05) respectively. This suggests a significant relationship between the genotypic distribution and OSF cases (P=0.040). The OR for CC is 2.56 with p-value = 0.040 that indicates that patients with CC gene have 2.56times higher risk for disease as compared to patients with CT and TT genotypes. Conclusion: The TGF-β1 gene polymorphism was shown to be statistically significantly associated with OSF. Keywords: TGF-β1 gene, Gene polymorphism, Oral sub mucous fibrosis.